Topological edge states of quasiperiodic elastic metasurfaces. (1st December 2022) - Pu, Xingbo; Palermo, Antonio; Marzani, Alessandro
Abstract: In this work, we investigate the dynamic behavior and the topological properties of quasiperiodic elastic metasurfaces, namely arrays of mechanical oscillators arranged over the free surface of a semi-infinite elastic medium according to a quasiperiodic spatial distribution. An ad-hoc multiple scattering formulation is developed to describe the dynamic interaction between Rayleigh waves and a generic array of surface resonators. The approach allows to calculate the spectrum of natural frequencies of the quasiperiodic metasurface which reveals a fractal distribution of the frequency gaps reminiscent of the Hofstadter butterfly. These gaps have nontrivial topological properties and can host Rayleigh-like edge modes. We demonstrate that such topologically protected edge modes can be driven from one boundary to the opposite of the array by a smooth variation of the phason, a parameter which modulates the geometry of the array. The proposed analytical framework could pave the way towards the design of devices for surface wave localization with applications in vibration mitigation and energy harvesting technologies.